Effects of Consumer Dispositional Attitude on Purchase Intention in an Emerging Market [version 3; peer review: 1 approved, 2 approved with reservations] - V. K. Ranjith; A. Venugopal Shanbhogue (F1000Research, 2024)
Background Globalization trends have compelled multinational companies to change their marketing approach from multi-domestic marketing to global marketing. This strategy has had a major impact on the branding of companies. Due to these efforts by international companies, there has been a negative impact on local brands. Strong local brands always maintained the advantage of a high level of awareness among consumers, due to consumers’ close relationship with these brands, hence this resulted in strong and positive marketing investments in the home market. The purpose of this research is to evaluate the attitudinal dispositions towards global and local brands and purchase intention. The objective is to understand the underlying motives of consumers’ purchase decision. Methods Consumer disposition and attitude towards brands are evaluated based on respondents’ purchase intention of a select brand. Data are collected from Bangalore and Chennai using the convenience sampling method. Evaluation of the measurement model was performed using the Smart PLS 4 software. Results Findings suggest that consumer attitudinal disposition has a significant impact on consumers’ purchase intention. Attitude formation is the first step in consumers’ behavioural decision and making a purchase decision. Marketing managers/practitioners need to focus on forming this attitude in consumers’ minds, so that this attitude formation leads to a purchase decision. Conclusions This research provides theoretical and managerial implications for marketers, especially those operating in an emerging market like India as this study has examined the role of consumer disposition on attitude formation and purchase intention. From a theoretical perspective, this study developed and tested a conceptual model describing the relationship between attitudinal disposition and purchase intention.